Application of impulse methods of weighting in the refractory capsules production process - V. T. Shmuradko; S. M. Usherenko; A. A. Andrushevich (Литьë и металлургия)
The article is devoted to the problem of manufacture of refractoty capsules of increased endurance out of difficult-to-extrude alloy powders made by impulse action method.